'A matter of commonsense': the Coventry poliomyelitis epidemic 1957 and the British public. Issue 3 (3rd July 2017) - Millward, Gareth
Abstract: In 1956, the British Ministry of Health instituted a vaccination programme against poliomyelitis, but run into myriad supply and administrative issues. When Coventry experienced an epidemic in 1957, it came to symbolise these problems. Throughout, it was claimed that the government lacked 'common sense'. This article explores how and why 'common sense' was used as a rhetorical weapon in the debates over policy at the local and national level. While those claiming 'common sense' were often at odds with medical and administrative authorities, the arguments were often informed by deeply held beliefs about vaccination and disease.